EXPLORATION OF QUEST-EXCURSIONS WITH THE HELP OF GEOINFORMATION SYSTEMS - Гринюк, Вікторія; Кіцелюк , Ірина Петрівна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
Quest tourism is a promising direction in youth tourism, which helps to increase interest in tourist objects with the help of the introduction of game technologies. Today, the tourist of the 21st century seeks to see something more than a traditional sightseeing excursion, therefore the relevance of the study is due to the need to develop and implement modern information systems in excursion activities for domestic tourism development, familiarization with the historical and cultural heritage of the city and the popularization of quest-excursions among residents and guests of Ivano-Frankivsk. The purpose of the article is to develop conceptual foundations for the organization of a quest-excursion using geoinformation technologies. The obligatory features of a quest-excursion were analyzed and it was determined that the main difference between a quest-excursion and a regular excursion is the interactivity of the process. Types of quests using modern information technologies, including geocaching, geotagging, and web quests, are considered. A quest-excursion has been developed using geoinformation technologies, namely geotagging, which will help the participants of the quest-excursion to navigate the city and quickly find tourist locations, tips and subsequent tasks based on geographical location. Maps of the tourist route were created for two teams of quest-excursion participants using GIS Google Maps, as well as maps with tourist objects that they must find by coordinates. Instructions for carrying out and criteria for evaluating the quest have been developed. The maximum number of points that each team can get is 58. The advantages of the developed tourist product are that the quest participants can gain new knowledge about the objects of historical and cultural heritage in the form of a game, solve unusual tasks, puzzles related to the history, culture and art of tourist locations of the city and will contribute to the development of erudition, attention and teamwork skills to achieve a common goal. Financial calculations of the quest-excursion cost and price have been made, which can be implemented in one of the Ivano-Frankivsk tourist companies in the future.